Czy moje ciało ucieleśnia poznanie? - Przemysław Nowakowski (Avant, 2012)
[Does my body embody cognition?] The works published in this section address the question of embodied cognition in an inspiring manner. In her article written ten years ago, Natika Newton deals with the notion of the relation between mental representation and embodiment. Frederique de Vignemont in his text written five years prior begins a strictly philosophical debate regarding the sense of ownership of one’s own body. Claire Petitmengin’s article is a kind of counterpoint to the previous texts. She attempts to explain and demonstrate the profound dimension of experience which she characterizes as affective, transmodal and gestural.